Diakonia and Healthcare's Contested Social Turn - Hordern, Joshua (Political theology, 2019)
Healthcare policy and practice is undergoing a major turn towards philosophy, the social world and responsiveness to persons. This turn opens up contested questions about what constitute goodness in healthcare. Answering these questions matters practically for understanding health-related social agency conducted by churches, ecclesial organisations and non-religious organisations. A revised understanding and practice of diakonia can speak apologetically into these matters. In this article, John N Collins' work is critically developed by interweaving the dual political and ecclesial senses of diakonia. The social authority of diakonia proceeds from its commissioned, representative nature and its eschatological, missional purposiveness. Thus conceived the duality of diakonia clarifies the conception and practice of health-related social agency and of service' more generally. The outcome is an Anglican political theology which avoids certain difficulties in German Protestants' concept and practice of Diakonie while addressing key issues raised in the other papers in this special issue.